2015
DOI: 10.1021/acs.jctc.5b00684
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Assumptions Underlying Continuum-Solvent Models

Abstract: Continuum-solvent models (CSMs) have successfully predicted many quantities, including the solvation-free energies (ΔG) of small molecules, but they have not consistently succeeded at reproducing experimental binding free energies (ΔΔG), especially for protein–protein complexes. Several CSMs break ΔG into the free energy (ΔGvdw) of inserting an uncharged molecule into solution and the free energy (ΔGel) gained from charging. Some further divide ΔGvdw into the free energy (ΔGrep) of inserting a nearly hard cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…A second effect is the higher density of Lennard‐Jones centers within a protein, compared to bulk solvent, leading to a systematic contribution to binding free energies. Following this picture, and analogous to the Lennard‐Jones model, it is tempting to divide the nonpolar contributions to solvation into (a) a repulsive short‐range interaction that occurs when one forms a solute‐shaped cavity and (b) the weak, attractive dispersion interactions between the solute atoms and the solvent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second effect is the higher density of Lennard‐Jones centers within a protein, compared to bulk solvent, leading to a systematic contribution to binding free energies. Following this picture, and analogous to the Lennard‐Jones model, it is tempting to divide the nonpolar contributions to solvation into (a) a repulsive short‐range interaction that occurs when one forms a solute‐shaped cavity and (b) the weak, attractive dispersion interactions between the solute atoms and the solvent …”
Section: Introductionmentioning
confidence: 99%
“…Following this picture, and analogous to the Lennard-Jones model, it is tempting to divide the nonpolar contributions to solvation into (a) a repulsive short-range interaction that occurs when one forms a solute-shaped cavity and (b) the weak, attractive dispersion interactions between the solute atoms and the solvent. [1,15,16] The above Lennard-Jones-like nonpolar contribution, along with GB provide a practical basis to develop and parameterize implicit solvent models. One model that is commonly used treats the polar component with a GB term and the nonpolar components with a surface area (SA) term.…”
Section: Introductionmentioning
confidence: 99%
“…However, because implicit solvent models perform this averaging in an approximate way, the accuracies of their predictions can be difficult to evaluate. [18,[22][23][24][25][26] In a recent article, we proposed a new implicit/explicit thermodynamic cycle that takes advantage of the speed of implicit solvent simulations but is designed to give the same answer as exhaustive sampling in explicit solvent. If a conformational transition of interest occurs faster in implicit solvent or vacuum or the simulation is simply faster in an implicit solvent model because of the many fewer degrees of freedom in the system, then we can estimate the desired free energy change on this auxiliary (implicit solvent or vacuum) free energy surface and obtain the free energy difference on our target (explicit solvent) free energy surface by connecting the two free energy surfaces with focused free energy calculations.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that these observations imply that γ rep should be greater for protein molecules than for alkanes because the average radii of curvature of proteins are larger than those of alkanes, and this conclusion would not be affected by noting that the proteins contain regions of negative curvature because such regions would also be associated with a larger γ rep in this model [6]. However, more recent studies [132, 133, 135] found that γ rep appears to decrease with A . Reconciling these findings would be difficult.…”
Section: Simple Theories Fail To Provide Quantitative Predictions mentioning
confidence: 99%
“…The integrand (〈∂ U att (0)/∂ λ 〉 λ ) of the integral used to compute the attractive component (Δ G att ) of the nonpolar solvation free energy as a function of λ for a barnase-barstar complex taken from a recent study [135]. …”
Section: Figurementioning
confidence: 99%